2012
DOI: 10.1016/j.colsurfa.2011.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aluminum fluoride complexation on fluoride removal by coagulation

Abstract: a b s t r a c tEffect of aluminum fluoride complexation on fluoride removal by Al salts coagulation was investigated by a series of batch experiments. Transformation of fluoride species in coagulation was studied by simultaneous determination of free fluoride and total fluoride at different pH and fluoride concentrations. Results showed that aluminum fluoride complexes dominated at low pH and high fluoride concentrations but more complexes did not represent higher fluoride removal. Comparison between coagulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 132 publications
(74 citation statements)
references
References 16 publications
4
68
0
2
Order By: Relevance
“…It was inferred that fluoride favored the formation of Al c . It was attributed to that the replacement of some hydroxyls by fluoride ions due to their similar chemical property contributed to the transformation of Al ions with less OH À to induce precipitation [7]. …”
Section: Al Species Distribution Of Different Al Coagulants Over Ph 4-9mentioning
confidence: 99%
See 4 more Smart Citations
“…It was inferred that fluoride favored the formation of Al c . It was attributed to that the replacement of some hydroxyls by fluoride ions due to their similar chemical property contributed to the transformation of Al ions with less OH À to induce precipitation [7]. …”
Section: Al Species Distribution Of Different Al Coagulants Over Ph 4-9mentioning
confidence: 99%
“…In this case fluoride removal was mainly attributed to physical adsorption and ion exchange effects [4,31], and the weakly acidic and acidic pH favored its removal. In B ranges from 1.0 to 1.5, PACl includes different Al species such as Al 2 , Al 4 , Al 7 and Al 13 et al [27], the ratios of monomeric Al species were observed to increase with lowered B. In this case coagulation dominated in the removal of fluoride, and different mechanisms such as complexed precipitation, charge attraction, and ion exchanges involve in and facilitated fluoride removal accordingly [32,33].…”
Section: Removal Efficiency Of Fluoride By Pacl With Different Basicitymentioning
confidence: 99%
See 3 more Smart Citations